MANAGEMENT ACCOUNTING AT THE BOUNDARY BETWEEN CLASSICAL AND MODERN - Andreea Paula DUMITRU; Cristina MATEI (Challenges of the Knowledge Society)
Deep changes in actual society have transformed management accounting information system in a ”black box”, the most important source of information on socio-economic context. Management accounting is a tool of counselor guidance providing management ”database” necessary management decision making. In these conditions, it is imperative abandon classical costing systems in favour of modern costing tailored to the requirements of modern management. But now, we live in a world of limited resources which require a rogorous analysis of the social, economic, cultural, historical entity that implements a specific systems costing. In this context, we believe it is useful to analyze the current trend of adopting modern costing systems at te expense of classical and adaptability of this reform in Romanian practice.